2004
DOI: 10.2190/ucj9-dp4m-9c0x-835m
|View full text |Cite
|
Sign up to set email alerts
|

Religious Struggle: Prevalence, Correlates and Mental Health Risks in Diabetic, Congestive Heart Failure, and Oncology Patients

Abstract: While further research is needed to help clarify the sources, additional correlates, and course of religious struggle, the findings in this study confirm the association between religious struggle and emotional distress in these three groups of medical patients. Clinicians should be attentive to signs of religious struggle. Where patient's responses indicate possible religious struggle, clinicians should consider referral to a trained, professional chaplain or pastoral counselor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
165
5
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(201 citation statements)
references
References 40 publications
21
165
5
7
Order By: Relevance
“…Numerous studies indicated that spirituality had a favorable impact on recovery, improved well-being (22,29,38,46,49), and lowered levels of depression (2,47). The positive effects of spirituality on health are thus more tangible (54,55), although using a positive religious compliance strategy does not necessarily reflect a lack of internal spiritual conflict (56).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicated that spirituality had a favorable impact on recovery, improved well-being (22,29,38,46,49), and lowered levels of depression (2,47). The positive effects of spirituality on health are thus more tangible (54,55), although using a positive religious compliance strategy does not necessarily reflect a lack of internal spiritual conflict (56).…”
Section: Discussionmentioning
confidence: 99%
“…26 Several other studies have reported varying levels of religiosity and religious coping among different socio-demographic categories including people of various socioeconomic status. [27][28][29][30][31][32] . In order to improve health care services and research, it is necessary to know how religiosity and religious coping are distributed among the clinical and general populations especially as this resource is widely available to Africans and people of low socio-economic status who may have more difficulties in accessing available health care.…”
Section: 18mentioning
confidence: 99%
“…Atualmente, as relações entre religiosidade e saúde -física e/ou mental -vêm sendo crescentemente investigadas [1][2][3][4][5][6][7] . A maior parte dos estudos indica que a religiosidade é habitualmente um fator de proteção contra o desenvolvimento de transtornos mentais (por exemplo, depressão, ansiedade, abuso de substâncias etc.)…”
Section: Introductionunclassified
“…Diversos fatores podem contribuir para um papel protetor da religião em relação à saúde mental, como: (1) a adoção de estilos de vida mais saudáveis 4 ; (2) o provimento de suporte social 5 ; (3) o desenvolvimento de um sistema de crenças e processos cognitivos que promovem maior aceitação de si e do próximo, com promoção de resiliência 6 e (4) condução de práticas religiosas que aliviam o sofrimento psicológico 2 . Por outro lado, em algumas circunstâncias, a religiosidade pode promover uma rígida disciplina comportamental, em que indivíduos com sofrimento psicológico podem desenvolver estratégias de enfrentamento pouco adaptativas (i.e., conflitos espirituais) [7][8][9] . No Brasil, um país no qual 95% da população declara ter religião, 83% consideram religião muito importante e cerca de 70% se dizem católicos 10 , o interesse no estudo da religiosidade e das suas relações com saúde física e mental tem aumentado progressivamente 11,12 .…”
Section: Introductionunclassified